The Effect of Diatomaceous Earth Addition on CBR Values of Glee Geunteng Soil in Aceh Besar, Aceh Province, Indonesia - Banta Chairullah; Munira Sungkar; Muhammad Ghiffari Ritonga (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2023)
The soil which is the platform often used for construction activities needs the strength to resist loads. However, its physical and mechanical properties are sometimes naturally limited and this implies there is a need for improvement and stabilization. Therefore, this study uses diatomaceous earth, which is a natural pozzolanic material classified as a type of Supplementary Cementing Materials (SCM), as an additive. The chemical stabilization was conducted by mixing the soil with stabilizing materials such as cement, lime, fly ash or others that have the ability to change the chemical composition and combination of soil. It is important to note that diatomaceous earth has similar properties as other pozzolanic materials such as fly ash and metakaolin powder and this is the reason it is expected to function as a soil stabilizing agent needed to improve soil properties. This study was conducted using the soil from Glee Geunteng in Peukan Bada as well as the diatomaceous earth obtained from Lambeureunut Village, Aceh Besar Regency, Aceh Province, Indonesia. The main purpose was to determine the California Bearing Ratio (CBR) value of the Glee Geunteng soil mixed with diatomaceous earth at 5, 10, 15, and 20% dry weight of the soil. The CBR test consisted of unsoaked CBR, soaked CBR testing at 4 days, and swelling properties of CBR with a variety of diatomaceous earth mixtures. Glee Geunteng soil was classified as A-6 Group Index 3 based on the AASHTO soil classification and as the SC (silty clay) soil according to the USCS classification. The results showed that the unsoaked CBR value reduced from 35.96% for the natural Glee Geunteng soil to 31.65% for the soil mixed with 20% diatomaceous earth material. A similar trend was observed for the soaked CBR value with a reduction from 15.57% to 6.98%. The decrease in CBR value was perceived to be caused by the very small silica content (SiO2 ) in diatomaceous earth material with 42.09% compared to the 86% in the material obtained from another source in the previous research by Hidayati.